Determination of craniofacial and dental characteristics of individuals with Williams‐Beuren syndrome by using 3D facial scans and radiographs. (21st October 2021) - Danneels, Florence; Verdonck, Anna; Indencleef, Karlijne; Declerck, Dominique; Willems, Guy; Cadenas De Llano‐Pérula, Maria
Abstract: Background: Williams‐Beuren syndrome (WBS) is caused by a microdeletion on chromosome 7q11‐23 and clusters a variety of systemic affectations. Aim: To investigate whether 3D facial scans can detect WBS by objectively addressing their craniofacial, skeletal and dental characteristics, compared with those of a non‐affected control group. Materials and Methods: 3D facial surface scans of 17 WBS individuals and 33 normal developing patients were analysed. Additionally, cephalometric and panoramic radiographs of subjects with WBS were compared with those of non‐affected individuals. Results: The 3D surface scans showed significant facial differences around the nose and mouth area. The cephalometric aspects of individuals with WBS differed mainly at the lower incisor region. Additionally, hypoplastic tooth morphology seems to be more often present in WBS. Conclusion: 3D images are a non‐invasive, efficient method to observe facial anomalies and facilitate an early diagnosis of WBS. Additionally, the analysis of the cephalometric and panoramic images revealed significant differences in dental characteristics. Together with early diagnosis through 3D images, these can help in the establishment of adequate medical, dental and orthodontic treatment planning.